The Ranking of Districts in Ouagadougou by the Risk of Flood and Runoff Using the PROMETHEE (European Journal of Pure and Applied Mathematics, 2019)
PROMETHEE methods are used for analyzing the risk of flood runoff in urban areas of Ouagadougou in Burkina Faso. 12 criteria are considered to calculate preference indices of the districts. We generated, on one hand, weights associated to these criteria taking into account hypotheses relatively to the importance or to the impact of each criterion evaluating the risk of flood runoff and on the other hand, we used the PROMETHEE methods to analyze this decision’s problem with its diverse criteria. The PROMETHEE I and PROMETHEE II are used ranking the districts in relation with the degree of risk of flood runoff.  This ranking is permitted by the calculated preference indices. Our aim is, on one hand   showing to the potential decision-maker the importance of such a multi-criteria analysis and on the other hand, of verifying the coherence of the hypotheses with the obtained weights.